The Impact of the US-China Trade War on Indonesia Exports and Foreign Direct Investment: A Systematic Literature Review - Maryam, Violita (LPPM Universitas Jambi, 2026)
The US-China trade war, which escalated significantly from 2018 and entered a new critical phase in 2025, has generated widespread implications for developing economies, including Indonesia. This study conducts a Systematic Literature Review (SLR) using the PRISMA 2020 protocol to synthesize evidence on the trade war impact on Indonesia export performance and FDI inflows during 2018-2026. From 312 Scopus-indexed documents, 45 articles met inclusion criteria (Q1-Q3 Scimago, all open access with verified DOIs). Thematic synthesis identified three dominant clusters: (1) export performance and trade diversion effects, (2) FDI and supply chain relocation dynamics, and (3) macroeconomic transmission mechanisms. Findings reveal ambivalent effects - negative pressure on primary commodity exports alongside positive investment diversion benefits - yet studies integrating both the pandemic and the 2025 tariff escalation remain sparse. Six research gaps are identified and a future research agenda is proposed.